2014
DOI: 10.2217/fmb.14.64
|View full text |Cite
|
Sign up to set email alerts
|

Biofilms in Periprosthetic Orthopedic Infections

Abstract: As the number of total joint arthroplasty and internal fixation procedures continues to rise, the threat of infection following surgery has significant clinical implications. These infections may have highly morbid consequences to patients, who often endure additional surgeries and lengthy exposures to systemic antibiotics, neither of which are guaranteed to resolve the infection. Of particular concern is the threat of bacterial biofilm development, since biofilm-mediated infections are difficult to diagnose a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
242
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(261 citation statements)
references
References 147 publications
4
242
0
6
Order By: Relevance
“…Future work, which will involve the design of clinically specific implants, will require a longer term release study to be conducted; the time frame of this study will be matched to the desired antibiotic delivery for the chosen clinical application. Typically when an infected implant is removed antibiotics are administered intravenously for 2-8 weeks [41]. Therefore it may be necessary to extend the period in which the antibiotic is released from the implant reservoir.…”
mentioning
confidence: 99%
“…Future work, which will involve the design of clinically specific implants, will require a longer term release study to be conducted; the time frame of this study will be matched to the desired antibiotic delivery for the chosen clinical application. Typically when an infected implant is removed antibiotics are administered intravenously for 2-8 weeks [41]. Therefore it may be necessary to extend the period in which the antibiotic is released from the implant reservoir.…”
mentioning
confidence: 99%
“…Furthermore, S. aureus strains produce stronger biofilm than P. aeroginosa. [1] We found that the NAC and teicoplanin show similar effects on S. aureus, with a significant decrease in the number of colonies formed (p<0.05). However, the combination of NAC with teicoplanin was more effective than NAC alone or teicoplanin alone.…”
Section: Discussionmentioning
confidence: 61%
“…Infections around the implant are among the most problematic issues of prosthetic medical care, and the treatment of a PJI that has a biofilm on the implant surface is almost impossible without removing the implant [1] In particular, biofilm produced by staphylococci are extremely difficult to eradicate.…”
mentioning
confidence: 99%
“…Biofilm formation in the arthroplasty milieu leads to high patient morbidity (McConoughey et al 2014). Despite, technical innovations, the rising cases of MRSA is a serious concern (Bassetti et al 2014).…”
Section: Disinfection Of Prosthetic Implantsmentioning
confidence: 99%